2022
DOI: 10.7150/ijms.69626
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of SK4 channels suppresses atrial fibrillation by attenuating atrial fibrosis in canines with prolonged atrial pacing

Abstract: Background: We previously found that intermediate conductance Ca 2+ -activated K + channel (SK4) might be an important target in atrial fibrillation (AF). Objective: To investigate the role of SK4 in AF maintenance. Methods: Twenty beagles were randomly assigned to the sham group (n=6), pacing group (n=7), and pacing+TRAM-34 group (n=7). Rapid atrial pacing continued for 7 days in the pacing and TRAM-34 groups. During the pacing, the TRAM-34 group received TRAM-34 intravenous injection (10 mg/Kg) 3 times per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…Our previous studies have revealed that during rapid atrial pacing in canines, the KCa3.1 expression in the atrium was enhanced. TRAM-34 completely blocked AF induction and suppressed electrical remodeling and atrial fibrosis development [ 21 , 23 ]. However, the effects of fibroblasts on KCa3.1 in atrial myocytes (AMs) are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have revealed that during rapid atrial pacing in canines, the KCa3.1 expression in the atrium was enhanced. TRAM-34 completely blocked AF induction and suppressed electrical remodeling and atrial fibrosis development [ 21 , 23 ]. However, the effects of fibroblasts on KCa3.1 in atrial myocytes (AMs) are unknown.…”
Section: Introductionmentioning
confidence: 99%